Optimizing Waste Combustion with Rocket Stove as an Environmentally Friendly Solution without Smoke - Fauzia, Dhiya; Mukti, Hidayat Nur; Andiansyah, Muhammad Ricky; Haris, Iglasia Amanda; Anggraeni, Dwi Septina; Salsabila, Putri Nur; Hasan, Reva Adilla; Bahri, Syaiful; Pramesty, Syafika Ayu; Bilqiis, Mahdelia Aqiilah; Mayasari, Winda Nur; Biky, Muhammad Amir; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
The practice of open waste burning in Nyalembeng Village, Pulosari Subdistrict, Pemalang Regency, causes air pollution and poses health risks to the community. This Community Service Program (Kuliah Kerja Nyata or KKN) aimed to optimize waste burning using a rocket stove as an environmentally friendly, smoke-free solution through a Participatory Action Research (PAR) approach. The program was conducted over one month and involved students, village officials, the Family Welfare Movement (PKK), and local residents. The stages included environmental mapping, planning, training, implementation, and evaluation. Training focused on waste separation, rocket stove operation, and education on the health impacts of open burning, with support from Pulosari Primary Health Center. Evaluation results showed an increase in participants’ average knowledge score from 51 to 85.3, alongside behavioral changes in waste management. The observed impacts included reduced open burning, minimal thick smoke, and improved air quality. The rocket stove innovation proved effective as both a technical and social solution to reduce pollution, enhance environmental awareness, and promote sustainable waste management at the village level.